2003
DOI: 10.1071/ea02101
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability effects on simulated pasture and animal production in the perennial pasture zone of south-eastern Australia.1. Between year variability in pasture and animal production

Abstract: Climate variability is a major constraint to farming in south-eastern Australia and one that is out of the farmers' control. However, a better understanding of long-term climate variability would be beneficial for on-farm management decisions. A series of long-term simulations were undertaken with the GrassGro decision support tool to determine the effect of climate variability on pasture and animal production at 6 locations in south-eastern Australia. The simulations ran from 89 to 119 years using daily weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Soil temperature was measured at 5 cm depth near the soil moisture probes (Decagon Device, Inc. model RT-1). The accuracy of the soil moisture sensors was improved by calibration following the method of Cobos and Chambers (2010). The sensors were grouped in soil moisture stations (SMS) at two sites: site 1 representative of hillslopes with Luvisols, and site 2 representative of the lower part of the catchment with shallow soils.…”
Section: Soil Moisture Content and Soil Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Soil temperature was measured at 5 cm depth near the soil moisture probes (Decagon Device, Inc. model RT-1). The accuracy of the soil moisture sensors was improved by calibration following the method of Cobos and Chambers (2010). The sensors were grouped in soil moisture stations (SMS) at two sites: site 1 representative of hillslopes with Luvisols, and site 2 representative of the lower part of the catchment with shallow soils.…”
Section: Soil Moisture Content and Soil Temperaturementioning
confidence: 99%
“…While abundant studies have applied numerical models to the study of grassland productivity (Montaldo et al, 2005;Istanbulluoglu et al, 2012) and some work has a focus on the spatiotemporal variability of pasture production over long periods (century scale) and large areas (Clark et al, 2003;Tubiello et al, 2007), to the authors' knowledge no studies have applied comprehensive mechanistic numerical models to address the questions posed above. Experimental or field studies have not addressed satisfactorily these questions either because pasture production over large areas is typically determined with a limited number of measurements commonly taken over a few years and at very specific locations (Plaixats et al, 2004;Santamaría et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A common problem for all crops and pastures is the occurrence of a 'false break' where sufficient rain falls to trigger germination but the subsequent soil moisture is insufficient to allow the seedlings to survive (Clark et al, 2003).…”
Section: Defining the Autumn Breakmentioning
confidence: 99%
“…Pasture growth, feed intake, cow liveweight, milk yield (autumn and spring), explore different management and risk scenarios, effect of dairy cow reproduction on farm economic performance. (Moore et al 2007) (Eckard et al 2006;Bryant et al 2007;Cullen et al 2007Cullen et al ,2008Chapman et al 2008;White et al 2008) (Berntsen et al 2005;Hutchings et al 2007) (Ándales et al 2005) (Hill et al 1999;Boschma & Scott 2000;Clark et al 2000Clark et al ,2003Cohen et al 2003;Salmon et al 2004;Bryant et al 2005;Robertson 2006) (Thornley & Verberne 1989;Thornley et al 1995;Cannell & Thornley 1998;Thornley & Cannell 2000;Thornley 2001;Barrettetal. 2004) (Rotz et al 1999b(Rotz et al ,c, 2003Sanderson et al 2001;Corson et al 2006Corson et al ,2007 (Cacho et al , 1999) Wastney et al 2002;Beukes et al 2005aBeukes et al ,b, 2007 was identified, the name of the model and the keyword "simulation" were entered as keywords in web of Knowledge®.…”
Section: Model Identificationmentioning
confidence: 99%
“…A pastoral farm agro-ecosystem model provides a means to test a number of different strategies before farmlet studies commence on the most successful strategies, thereby reducing costs (Hart et al 1998). Pastoral farm agro-ecosystem models have been used in multiple applications (see Table 1) ranging from predicting animal responses from plant data measured in small plots (Boschma & Scott 2000), predicting animal performance and pasture production at multiple sites incorporating 50-100 years of daily weather data (Clark et al 2003), testing hypotheses and deducing immeasurable parameters (Bywater & Cacho 1994) and determining within-year and year-to-year variations, and theoretical minimum and maximum nitrogen leaching, pasture growth, and drainage ). Full-scale field studies to examine such issues may not be feasible due to the limited size of plot areas or time and financial constraints.…”
Section: Introductionmentioning
confidence: 99%